Commercial bank small business lending pre and post crisis - Kevin T. Jacques; Richard Moylan; Peter J. Nigro (The Journal of Entrepreneurial Finance (JEF), 2016)
We analyze small business lending at U.S. commercial banks, how it has changed over time and how it differs by bank size. Specifically, we examine the impact of government policy intervention on small business lending in the aftermath of the financial crisis. We find several important results. First, we find that the Troubled-Asset Relief Program's (TARP) 200 billion Capital Purchase Program (CPP) had little impact on the banks that received capital injections' small business lending. Second, the Small Business Loan Fund (SBLF) lending program appears to have been a success as banks participating in the loan fund increased their lending to small businesses. Finally, we find that financial turmoil had a substantial negative impact on lending to small businesses at community banks but not their large bank counterparts. This result suggests that the larger banks may have behaved in a manner consistent with too big to fail. Collectively, these results provide important insights for policy makers as they continue to deal with the credit access issues of small firms.
Keywords: G21; G18; G01; E58; 650; small business lending; financial crisis; credit crunch; TARP; Small Business Loan Fund; Financial Stress